Mutual Reciprocal Interconnection of Relations Describing Creep, Yield Stress and Stress Relaxation - Kohout, Jan; Hruby, Vojtech (Communications - Scientific letters of the University of Zilina, 2010)
The steady-state creep rate increases with testing temperature according to the Arrhenius law and its increase with applied stress is usually described by the power law. Simple multiplication of these two laws leads to the dependence of steady-state creep rate on both the variables. Apparent activation energy and stress sensitivity parameter perform in the combined law as constants but most measurements show their dependence on some of the variables. An equation respecting these experimental facts and simultaneously also based on the Arrhenius equation and the power law is derived and verified using some published results of creep tests. It can be presented geometrically by hyperbolic paraboloid. Resulting from this equation, the dependence of yield stress on temperature and strain rate and also an equation describing the relaxation curves are deduced.